2020
DOI: 10.1016/j.jat.2020.105456
|View full text |Cite
|
Sign up to set email alerts
|

Atomic norm minimization for decomposition into complex exponentials and optimal transport in Fourier domain

Abstract: This paper is devoted to the decomposition of vectors into sampled complex exponentials; or, equivalently, to the information over discrete measures captured in a finite sequence of their Fourier coefficients. We study existence, uniqueness, and cardinality properties, as well as computational aspects of estimation using convex semidefinite programs. We then explore optimal transport between measures, of which only a finite sequence of Fourier coefficients is known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…, t fc−1 }. Since that set is equispaced in T, we notice as in [Con19] that, to recover the amplitudes a j , we may invert the system Since the function cotan is (strictly) decreasing on ]0, π[, we see that a ℓ = 0 with sign(a ℓ ) = sign(η * (t ℓ )), which is the desired optimality condition. It remains to check that (33) also holds for k = f c .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…, t fc−1 }. Since that set is equispaced in T, we notice as in [Con19] that, to recover the amplitudes a j , we may invert the system Since the function cotan is (strictly) decreasing on ]0, π[, we see that a ℓ = 0 with sign(a ℓ ) = sign(η * (t ℓ )), which is the desired optimality condition. It remains to check that (33) also holds for k = f c .…”
Section: Discussionmentioning
confidence: 99%
“…where {ϕ k } 2fc k=0 is again the trigonometric system. In [Con19], Laurent Condat has observed that when y is the Fourier coefficient vector of two opposite close spikes, a solution to (28) is a Dirac comb. More precisely, if y = Φm 0 def.…”
Section: The Carathéodory Numbermentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, we use trigonometric moments, or Fourier coefficients. The characterization of a measure on the circle from a subset of its Fourier coefficients has a long history, rooted in Carathéodory's work [24]; in short, the latter constraint is satisfied if the Toeplitz matrix formed by the c m is positive semidefinite [25], [26].…”
Section: Moments Of Measuresmentioning
confidence: 99%